Pembelajaran Praktik Teknik Pengolahan Gerak Legaran Galombang Randai - Hendri Yusuf; Indra Yuda (Peneliti.net, 2020)
Randai is a miniature traditional Minangkabau performing art which has complete elements of traditional performing arts. As a complete miniature of Minangkabau performing arts, in the randai performance there are elements of literary art in the form of a script containing dialogues expressed in Minangkabau language and literature, music art expressed by chanting sounds of chanting or classical Minangkabau saluang songs, movement arts or dance which is expressed through the movements of the pasambahan, the motion of galombang legaran Randai which originates from the basic movements of the Minangkabau style of pencak silat, and the art of teter which is expressed by. Apart from the main elements of the performing arts in randai, there is also visual art as a supporting element for the perfection of the randai performance. Movement is the most important element in carrying out the randai performance. The randai show begins with motion, in the middle contains motion, the closing part of the randai show ends with motion. Along with the development of science, the accommodation of local arts becomes a part of which is studied at formal education centers, such as elementary, junior high, high school and even higher education in West Sumatra. As an art that is studied in formal education, of course, it is necessary to provide written media in the form of tutorials to help or as a companion in learning the techniques of clever movements in colleges and the wider community. Based on this background, the writer tries to parse the problem of how or the technique of processing the galombang randai motion. Although randai motion is dynamic and has a wide variety and richness of motion motives, this tutorial is a technical guide, not uniform.